Development of predictive models for paediatric unplanned hospital readmissions: A mixed-methods sequential explanatory study at a tertiary children’s hospital in Western Australia - Zhou, Huaqiong (Curtin University, 2021)
A mixed-methods sequential explanatory research design, collecting quantitative and qualitative data, examined paediatric unplanned hospital readmissions and nurse-caregiver communication of hospital-to-home transition information at a tertiary children’s hospital in Western Australia. The thesis is presented as seven peer-reviewed journal publications, including three comprehensive literature analyses and four primary studies. Research outcomes confirmed the complexities associated with developing predictive models, inconsistent content and delivery of transition information and the need to implement a comprehensive transition framework.